Нелинейная нестационарная теплопроводность стенки при граничных условиях III рода - Драганов, Б. Х. (Energy and Automation, 2017)
UDC 621.1.0164(03)NONLINEAR TRANSIENT HEAT CONDUCTION WALL IN KIND BOUNDARY CONDITIONS III.B. DraganovAnnotation. A method for solution of nonlinear transient heat transfer through a single and multi-layer wall for the boundary of channel III kind. For the formulation of a problem solving method is used on the basis of the provisions of the promptness of a small parameter and finite integral transformation.Keywords: nonlinear transient heat transfer, small parameter method, the specific heat, the coefficient of linear dependence, the integral transformation of the boundary conditions The purpose of research - to develop a method for solving the nonlinear unsteady heat transfer problem through single and multi-layered wall.Experience has shown that for many materials the dependence of thermal characteristics of temperature is linear over a sufficiently wide range of temperature changes.All three received linearized problems were solved by the finite integral transformations.As a result of the application of this method of finite integral transformations of the heat equation in the image will go into an ordinary differential equation of the first order.For multi-layer walls used the method of solution of nonlinear transient heat conduction problems on the basis of joint small-parameter method and finite integral transformation.Analysis of the results of research based thermal performance of building materials on temperature showed the possibility of approximation by linear functions of the temperature range, typical for the real conditions of use of buildings. This factor depends bridge thermal conductivity and specific heat of the temperature of the order of 10-3.